Democratic Backsliding in Nigeria: A Comparative Assessment of Institutional Decline in West Africa - Yemi Daniel Ogundare; Nyam Elisha Yakubu (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
This article examines the phenomenon of democratic backsliding in Nigeria through an institutional lens, comparing its trajectory with those of selected West African peers. We begin by surveying the literature on democratic erosion and institutional decay in Africa, noting that formal democratic rules often mask autocratic practices. Theoretical perspectives such as Democratic Consolidation Theory and Institutional Theory are applied to explain Nigeria’s institutional erosion. Using a qualitative comparative case study approach, we analyze Nigeria’s recent decline focusing on the judiciary, electoral processes, and executive-legislative relations drawing on empirical data from election observer reports and scholarly studies. We then contrast these findings with developments in Ghana, Senegal, and Mali to identify regional patterns. The analysis reveals that while Ghana’s democracy remains relatively robust, both Senegal and Mali have experienced acute reversals, highlighting a regional trend of weakening checks and rising authoritarianism. We discuss the implications for governance and security in West Africa, noting that institutional decay undermines public trust and can exacerbate conflict. The article concludes with policy recommendations strengthening judicial independence, reforming electoral bodies, protecting civil liberties, and bolstering regional democratic norms to promote resilience against backsliding. These recommendations aim to guide reformers in sustaining democratic governance in Nigeria and the region.